Surgical repair of rectovaginal fistulae in mares: Twelve cases (1983-1991) - Desjardins, Marc R. (1993)
The case records of 12 mares at the Ontario and Atlantic Veterinary Colleges were reviewed to evaluate the success rates of surgical techniques used to repair rectovaginal fistulae. A modified horizontal perineal technique was used in eight mares; it was unsuccessful in one mare, but the fistula was subsequently successfully repaired using the same technique. One rectovaginal fistula that was converted to a third-degree perineal laceration was successfully repaired on the third attempt, using the suture principles of the modified horizontal perineal technique. A modified transvaginal technique was used in three mares, in two of which it failed; their fistulae were subsequently converted to third-degree perineal lacerations and repaired using a one-stage closure. We conclude that the modified horizontal perineal technique is a one-stage procedure that is technically easy to perform, results in less tension on the suture lines, and is effective in modifying poor vulvar conformation.